Completing the Puzzle: A Cluster of Hunting Dogs with Tick-Borne Illness from a Fishing Community in Tobago, West Indies - Roxanne A. Charles; Patricia Pow-Brown; Annika Gordon-Dillon; Lemar Blake; Soren Nicholls; Arianne Brown-Jordan; Joanne Caruth; Candice Sant; Indira Pargass; Asoke Basu; Emmanuel Albina; Christopher Oura; et al. (Pathogens, 2024)
Eight hunting dogs were visited by a state veterinarian on the island of Tobago, Trinidad and Tobago, West Indies, as owners reported anorexia and paralysis in five of their dogs. The veterinarian observed a combination of clinical signs consistent with tick-borne illness, including fever, anorexia, anaemia, lethargy and paralysis. Blood and ticks were collected from each dog and submitted to a diagnostic laboratory for analysis. Microscopic analysis revealed a mixed infection of intracytoplasmic organisms consistent with Babesia spp. (erythrocyte) and Ehrlichia spp. (monocyte), respectively, from one dog, while a complete blood count indicated a regenerative anaemia (n = 1; 12.5%), non-regenerative anaemia (n = 4; 50%), neutrophilia (n = 3; 37.5%), lymphocytosis (n = 2; 25%), thrombocytopaenia (n = 3; 37.5%) and pancytopaenia (n = 1; 12.5%). DNA isolated from the eight blood samples and 20 ticks (16 Rhipicephalus sanguineus and 4 Amblyomma ovale) were subjected to conventional PCR and next-generation sequencing of the 16S rRNA and 18S rRNA gene for Anaplasma/Ehrlichia and Babesia/Theileria/Hepatozoon, respectively. The DNA of Ehrlichia spp., closely related to Ehrlichia canis, was detected in the blood of three dogs (37.5%), Anaplasma spp., closely related to Anaplasma marginale, in two (25%), Babesia vogeli in one dog (12.5%) and seven ticks (35%) and Hepatozoon canis and Anaplasma spp., in one tick (5%), respectively. These findings highlight the need to test both the vector and host for the presence of tick-borne pathogens when undertaking diagnostic investigations. Further studies are also warranted to elucidate the susceptibility of canids to Anaplasma marginale.